Fish intake and risk of chronic obstructive pulmonary disease in 2 large US cohorts. Issue 2 (26th November 2014) - Varraso, Raphaëlle; Barr, R Graham; Willett, Walter C; Speizer, Frank E; Camargo, Carlos A
ABSTRACT: Background: Despite mechanistic data that linked fish and omega-3 (n–3) PUFAs with lower risk of chronic obstructive pulmonary disease (COPD), epidemiologic data remain scarce. Fish and n–3 PUFAs are an important component of the prudent dietary pattern that is thought to be protective in the onset of COPD. Objective: We examined the role of fish and PUFA intakes on risk of developing COPD while taking into account the overall dietary pattern. Design: We investigated the objective in 120, 175 women and men from the Nurses' Health Study and Health Professionals Follow-Up Study. Over the study period (1984–2000), there were 889 cases of newly diagnosed COPD. Cumulative average intakes of fish, eicosapentaenoic acid, docosahexaenoic acid, n–3 PUFAs, n–6 PUFAs, and the n–3:n–6 ratio were calculated from repeated food-frequency questionnaires. Because fish is a food group included in the prudent pattern, we derived a new prudent pattern without the contribution from fish, and we termed this pattern the "modified prudent" pattern. We performed multivariable Cox proportional hazards models. Results: Before the dietary pattern was taken into account, and with 14 factors controlled for, we showed that more-frequent fish intake (≥4 servings/wk) was inversely associated with risk of COPD [adjusted pooled HR for the highest intake compared with the lowest intake (<1 serving/wk): 0.71; 95% CI: 0.54, 0.94]. After additional adjustment for the dietary pattern (modified prudent and Western patterns), the association was NS (0.84; 95% CI: 0.63, 1.13). No significant associations were shown between PUFA intakes and risk of COPD. Conclusion: Although COPD-prevention efforts should continue to focus on smoking cessation, these prospective findings support the importance of promoting a healthy diet in multi-interventional programs to prevent COPD instead of focusing on changes in an isolated food or nutrient.